Tác động của chính sách phúc lợi bắt buộc dành cho người lao động đến năng suất lao động của các doanh nghiệp nhỏ và vừa Việt Nam - Đào Vũ Phương, Linh; Phạm Khánh, Nam; Lê Văn, Chơn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
Although there is a vast literature on the relationship between labor compensation and firm productivity, economists in Vietnam mainly focus on salary structure which still appears ineffective. Moreover, a little attention has been given to non-monetary benefits for employees. This study investigates the impact of non-wage welfare policy on labor productivity among small and medium-sized enterprises (SMEs) which are currently playing a vital role in the Vietnamese economy. We used fixed effect model (FEM) and random effect model (REM) estimation with instrumental variables is applied to a panel dataset extracted from 2011–2015 SMEs surveys conducted by the Central Institute for Economic Management (CIEM). The author find that non-wage benefits in SMEs have a significant impact on labor productivity. However, the impact can be positive or negative depending on different reasons.
Keywords: Employee benefits; Labor productivity; Non-wage welfare; Small and medium enterprises